The Effectiveness of Canva-Based DIY Presentations in Enhancing English-Speaking Performance - Ayusasmita, Via; Wahyuni, Sri; Bahri, Seful (Dinasti Publisher, 2025)
Improving students’ English-speaking skills remains a persistent challenge in Indonesia, particularly in traditional classroom settings. This study explores the effectiveness of Canva-based Do-It-Yourself (DIY) projects, specifically procedural text presentations, as a pedagogical tool to enhance speaking performance. Utilizing a mixed-methods approach, the research integrates quantitative data from pre-tests, treatments, and post-tests. Canva-based DIY presentations served as the independent variable, while students’ speaking performance was the dependent variable. Statistical analysis, conducted via SPSS, revealed a significant improvement: a 26.08-point increase in speaking scores, a rise in post-test completion rate from 0% to 64.3%, and a p-value of 0.000 (<0.05), confirming the effectiveness of the intervention. Students also reported increased motivation, creativity, and confidence, despite minor technical hurdles. These findings suggest that Canva offers a low-cost, visually rich platform to stimulate learner engagement and support the development of key speaking sub-skills: grammar, pronunciation, vocabulary, and fluency. However, the study’s small sample size and limited classroom context constrain its generalizability. Future research should involve broader populations and longitudinal designs to validate long-term impacts.